Desafios e Propostas para a Governança Participativa no SUS: Conselhos de Saúde em Regiões Rurais e Ribeirinhas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Local health councils are essential instruments of participatory governance in the Unified Health System, connecting public management to community demands. In rural and riverside regions, the effectiveness of these councils is often compromised by logistical barriers, regulatory limitations, and representation challenges. This qualitative study analyzes the impact of these difficulties and proposes solutions based on Resolution n° 714/2023 of the National Health Council, including regulatory flexibility, regionalized training programs, and specific funding. The results highlight the need for adaptations that consider local particularities, strengthening social inclusion and equity in the SUS. We conclude that health councils strengthen governance in the SUS, contributing significantly to the formulation of contextualized public health strategies. By proposing practical measures inspired by international experiences, the article offers support for more effective and inclusive public policies.
Keywords: Governança em Saúde; Sistema Único de Saúde; Políticas de Controle Social; CNPQ:: CIÊNCIAS DA SAÚDE